2014
DOI: 10.1177/0300985814542812
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Papillomavirus in a Northern Fulmar (Fulmarus glacialis) With Viral Production in Cartilage

Abstract: We report the identification of a novel papillomavirus, Fulmarus glacialis papillomavirus 1 (FgPV1), present within an interdigital foot mass of a Northern Fulmar (Fulmarus glacialis). The mass of interest was composed of normal stratified and keratinized epithelium and dense mesenchymal cells with central cartilaginous islands. Within the nuclei of many chondrocytes were loose aggregates or paracrystalline arrays of virions approximately 50 nm in size. Degenerate polymerase chain reaction was used to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
(62 reference statements)
4
20
0
Order By: Relevance
“…Combining the inconclusive phylogenetic clustering with this additional molecular morphology data enables us to hypothesize that FgPV1 diverged from the other sauropsid papillomaviruses before the avian-turtle host animal diverged. This conclusion is further supported by the observation that FgPV1 lesions are uniquely associated with cartilage, while all other known papillomaviruses are primarily epithelial trophic ( Gaynor et al 2015 ).…”
Section: Resultsmentioning
confidence: 68%
See 3 more Smart Citations
“…Combining the inconclusive phylogenetic clustering with this additional molecular morphology data enables us to hypothesize that FgPV1 diverged from the other sauropsid papillomaviruses before the avian-turtle host animal diverged. This conclusion is further supported by the observation that FgPV1 lesions are uniquely associated with cartilage, while all other known papillomaviruses are primarily epithelial trophic ( Gaynor et al 2015 ).…”
Section: Resultsmentioning
confidence: 68%
“…However, the E6 proteins of all known sauropsid papillomaviruses contain only one such motif. Since the fish papillomavirus (SaPV1) does not contain any such motif ( Gaynor et al 2015 ), it is likely that the most recent common ancestor of the mammalian and sauropsid papillomaviruses had a single motif E6, which duplicated to give rise to the mammalian papillomavirus double Zinc finger motif in E6 ( Van Doorslaer et al 2009 ). The sauropsid (putative) E7 protein may be even more remarkable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These data suggest that BPV-infected cell lines are a useful model to study the pathogenic mechanisms that lead to cancer. Our contribution has allowed to know the BPV prevalence and distribution in Brazil (Diniz et al , 2009; Carvalho et al , 2013; Lunardi et al , 2013; Melo et al , 2014; Araldi et al , 2014b; Cota et al , 2015; Gaynor et al , 2015a; Grindatto et al , 2015; Dong et al , 2016; Martano et al , 2016). These studies showed that the co-infection of at least two BPV types is frequent (Araldi et al , 2013, 2014a; Carvalho et al , 2013), demonstrating the importance to develop multivalent vaccines.…”
Section: Breaking Paradigmsmentioning
confidence: 99%